Porous and single crystalline Co3O4 nanospheres for pseudocapacitors with enhanced performance. Issue 35 (16th March 2015) - Gong, Yuyin; Gong, Feilong; Wang, Chaofei; Zheng, Hegen; Li, Feng
Abstract : Co3 O4 supercrystals for pseudocapacitors: the stepwise splitting of nanocuboids can generate porous and single crystalline Co3 O4 hemispheres with highly enhanced performances in storing charges. Abstract : Porous and single-crystalline Co3 O4 nanospheres have been synthesized successfully on a large scale. It was found that the reaction time can dramatically affect the growth of the Co3 O4 nanospheres in nanoreactors constructed with AOT − and Co 2+ ions. The dynamic evolution of the nanostructures produced in the reaction strongly support a stepwise splitting mechanism proposed to explain the formation of the porous and single crystalline nanospheres. The pseudocapacitors made with the porous and single crystalline Co3 O4 nanospheres exhibit excellent charge-storage performance. The enhanced electrochemical properties of the materials can be attributed to their superstructures with pores and single crystalline features.